Optimizing short-term maximal exercise performance: the superior efficacy of a 6 mg/kg caffeine dose over 3 or 9 mg/kg in young female team-sports athletes - Bougrine, H.; Ammar, A.; Salem, A.; Trabelsi, K.; Jahrami, H.; Chtourou, H.; Souissi, N. (Nutrients, 2024)
Caffeine (CAF) is among the most extensively researched dietary supplements worldwide. However, little is known about the relationship between dosage and performance enhancement, particularly in female athletes. This study aimed to explore the effects of three different CAF dosages (3 mg·kg-1, 6 mg·kg-1, and 9 mg·kg-1) on high-intensity exercise and the prevalence of undesirable side effects related to these doses among female team-sports athletes. All participants (n = 16; age: 16.9 ± 0.6 y; height: 1.64 ± 0.1 m; BMI: 21.6 ± 1.5 kg·m-2) were mild CAF consumers. This study had a randomized, crossover, double-blind design in which each athlete performed four experimental sessions after ingesting either a placebo (PLAC), 3 mg·kg-1 CAF (CAF-3), 6 mg·kg-1 CAF (CAF-6), or 9 mg·kg-1 of CAF (CAF-9), with an in-between washout period of at least 72 h. In each experimental session, 60 min after ingesting the capsules, participants underwent a countermovement jumps test (CMJ), modified agility t-test (MATT), repeated sprint ability (RSA) test, and a rating of perceived exertion (RPE) and completed the CAF side effects questionnaire. Our findings revealed that in comparison to the PLAC condition, the MATT, RSAmean, and RSAbest performances were significantly greater only under the CAF-6 and CAF-9 conditions. Although the RPE scores remained unchanged, CMJ performance improved under all CAF conditions. All the performance outcomes were better for the CAF-6 and CAF-9 conditions than for the CAF-3 condition. Notably, no significant difference between the CAF-6 and CAF-9 conditions was observed for any of these parameters despite the highest incidence of side effects being noted for the CAF-9 condition. In summary, our findings highlight the recommendation for a moderate CAF dosage of 6 mg·kg-1 rather than 3 or 9 mg·kg-1 to enhance various aspects of short-term maximal performance in mild-CAF-consumer female team-sports athletes while mitigating the occurrence of adverse CAF side effects.